Role of central vagal 5-HT3 receptors in gastrointestinal physiology and pathophysiology - Browning, Kirsteen N. (Frontiers in Neuroscience, 2015)
Vagal neurocircuits are vitally important in the co-ordination and modulation of GI reflexes and homeostatic functions. 5-hydroxytryptamine (5-HT; serotonin) is critically important in the regulation of several of these autonomic gastrointestinal (GI) functions including motility, secretion and visceral sensitivity. While several 5-HT receptors are involved in these physiological responses, the ligand-gated 5-HT3 receptor appears intimately involved in gut-brain signaling, particularly via the afferent (sensory) vagus nerve. 5-HT is released from enterochromaffin cells in response to mechanical or chemical stimulation of the GI tract which leads to activation of 5-HT3 receptors on the terminals of vagal afferents. 5-HT3 receptors are also present on the soma of vagal afferent neurons, including GI vagal afferent neurons, where they can be activated by circulating 5-HT. The central terminals of vagal afferents also exhibit 5-HT3 receptors that function to increase glutamatergic synaptic transmission to second order neurons of the nucleus tractus solitarius within the brainstem. Thus, activation of 5-HT3 receptors may modulate the excitability and activity of gastrointestinal vagal afferents at multiple sites and may be involved in several physiological and pathophysiological conditions, including distention- and chemical-evoked vagal reflexes, nausea and vomiting, as well as visceral hypersensitivity